2010
DOI: 10.1103/physrevlett.104.126403
|View full text |Cite
|
Sign up to set email alerts
|

Gain-Induced Trapping of Microcavity Exciton Polariton Condensates

Abstract: In this letter, we present a study of the condensation of exciton-polaritons in large etched pillar structures that exhibit shallow edge trapping. The ≈ 100 µm ×100 µm pillars were fabricated using photolithography and a BCl 3 /Cl 2 reactive ion etch. A low energy region emerged along the etched edge, with the minima ≈ 7 µm from the outer edge. The depth of the trap was 0.5 − 1.5 meV relative to the level central region, with the deepest trapping at the corners. We were able to produce a Bose-Einstein condensa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 16 publications
4
62
0
Order By: Relevance
“…multimode pump laser modulate the reservoir population strongly, this results in modulation of the local interaction energy and thus of the local phase of the condensate, which induces a separation of the vortex and antivortex. We confirmed that a vortex-antivortex pair is not regularly generated when a quiet single-mode pump laser is used 22 . We also note that thermal effects are not strong enough to spontaneously create a vortex-antivortex pair in our system.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…multimode pump laser modulate the reservoir population strongly, this results in modulation of the local interaction energy and thus of the local phase of the condensate, which induces a separation of the vortex and antivortex. We confirmed that a vortex-antivortex pair is not regularly generated when a quiet single-mode pump laser is used 22 . We also note that thermal effects are not strong enough to spontaneously create a vortex-antivortex pair in our system.…”
supporting
confidence: 64%
“…The incident power is controlled by a polarization filtering set-up employing a variable retarder, as in ref. 22. The threshold power of 20 mW (see Supplementary Information) gives a threshold particle density of ∼10 2 µm −2 for our 20-µm-diameter pumping spot, given the 4 ps lower-polariton lifetime, and estimated pumping efficiency of 15%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such oscillations also occur in the dissipationdominated regime, where they reflect the coexistence of two condensates of different frequencies, as in a multimode laser [19]. Indeed at the qualitative level many important phenomena, like gap solitons [14,15], vortices [16], and condensate localization [17,24,25], occur in both interaction-dominated and dissipation-dominated condensates.…”
Section: Introductionmentioning
confidence: 99%